Adherence to postpartum diabetes mellitus screening, do associated pregnancy complications make a difference?. (January 2020) - Rotem, Reut; Salem-Yaniv, Simrit; Sandler-Rahat, Hadar; Yohay, David; Sade, Shanny; Yahav, Lior; Weintraub, Adi Y.
Abstract: Aims: We aimed to investigate the impact of Gestational Diabetes Mellitus (GDM) complications on compliance with postpartum Diabetes screening. Methods: A retrospective cohort study was conducted comparing screening rates of women with and without GDM associated complications who delivered at the Soroka University Medical Center, between 2016 and 2017. The screening test of choice was a 2-hour 75 g oral glucose tolerance test, taken 6–12 weeks after delivery. GDM associated complications included one or more of the following: polyhydramnios, macrosomia, shoulder dystocia or cesarean section. Univariate analysis was used in order to examine if GDM associated complications were associated with postpartum diabetes screening. Results: During the study period a 164 women were included, of which, 82 women had suffered from GDM associated complications and comprised the study group and 82 women with GDM but without complications comprised the comparison group. Women in the study group were significantly older with a higher parity order. Induction rates were significantly higher among the comparison group, whereas, cesarean section rates were higher among the study group. No difference was noted with regard to neonatal outcomes. Women in the study group were not found to be more likely to be given screening recommendations at discharge (P = 0.50), at their postpartum visit (P = 0.36) or to perform DM screening postpartum (P = 0.17). Conclusion: Women with GDM associated complications had a higher rate of compliance to postpartum DM screening recommendations. However, in the current study this difference did not reach statistical significance.